Analisis Pemanfaatan e-Learning di Masa Pandemi (Studi Kepustakaan: Learning Loss pada Peserta Didik) - Donna Rhamdan; Atrendy Kule; Sucahyo Mas'an Al Wahid (STKIP PGRI SITUBONDO, 2021)
Learning loss is an educator's concern for students, the loss of learning both cognitively with the achievement of competencies that should be achieved comprehensively but partially achieved. It can also be in the form of loss of motivation to learn, one of the methods used is utilizing e-learning and the development of interesting learning media for students. This study aims to reveal the ways that can be chosen to maximize the benefits of e-learning, considering the development of e-learning is very fast despite the advantages and disadvantages of its use. The research that will be conducted uses qualitative research methods with a literature study approach. The research stages include the type of library, reviewing library materials, and recommendations. The subject of this research is the researcher himself with the help of various types of literature reviews such as books and research articles. The data obtained is in the form of e learning recommendations that can reduce the impact of learning loss. The results of the research based on the literature study show that Learning Loss is found in many countries with reading problems compared to other things that have always been a scourge for subjects outside of literacy and numeracy understanding. Then e-learning can be presented by knowing in advance the needs of students to reduce boredom and perceptions in the use of platforms and applications, then popular e-learning activities in the form of online whiteboards, as well as STAD and PBL learning models that are used in the implementation of e-learning to improve learning outcomes. language skill.